Content and Language Integrated Learning (CLIL) in science class during covid-19 outbreak: A narrative inquiry - Rina Wahyu Setyaningrum; Slamet Setiawan; Syafiul Anam; Pratiwi Retnaningdyah (English Review: Journal of English Education, 2020)
COVID-19 outbreak that has shifted face-to-face (f2f) to forced remote learning challenged the CLIL Science teacher to thrive in a new teaching form. The f2f adaptation of the virtual meeting using video conferencing software has driven the teacher to have an effective and accessible synchronous learning environment, in addition to the asynchronous one. This research was a narrative inquiry participated by a CLIL Science teacher teaching the first-grader in a small town in Indonesia. By employing an in-depth interview, the data were collected and then analyzed by emotional geography frameworks. The findings showcased the f2f adaptations made by the teacher that synchronous mode of delivery was conducted in thirty minutes by careful attention on CLIL frameworks, the language (s) use, and students’ engagement. Her sociocultural, moral, professional and political geographies led her to decide what to do to make the students learning feasible. An implication of this is the possibility that the experience of how the CLIL Science teacher taught the young learners using English would be a new insight for other teachers in dealing with real-time live lesson delivery during the COVID-19 outbreak.